DISCON: A New Method for the Layout Problem - Drezner, Zvi (Operations Research, 1980)
Layout problems often involve a given number of facilities which must be located in the plane. Each of these facilities has a given area, and the cost of interactions between every facility pair is known. Problem optimality is achieved when facilities do not overlap and the total cost, which is the sum of weighted distances between all pairs of facilities, is minimized. The problem is formulated and solved as a nonconvex mathematical programming problem using a procedure termed DISpersion-CONcentration.